2012
DOI: 10.1021/jf3032556
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Citrus Flavonoids on Starch Digestion and Antihyperglycemic Effects in HepG2 Cells

Abstract: Flavonoids are a class of important bioactive natural products and are being extensively used in functional foods. In the present study, the effects of four Citrus flavonoids (i.e., hesperidin, naringin, neohesperidin, and nobiletin) on amylase-catalyzed starch digestion, major digestive enzyme activities (e.g., pancreatic α-amylase and α-glucosidase), and glucose use in HepG2 cells were investigated. The results showed that all of the tested Citrus flavonoids significantly inhibited amylase-catalyzed star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 50 publications
4
75
1
2
Order By: Relevance
“…In fact, many phenolic compounds and specially flavonoids have been reported as potential antidiabetic agents because they exert a good inhibitory action against α-amylase and could have potential prevention in diabetes mellitus as part of a dietary strategy [49]. These results were confirmed by others studies which showed that all of the tested Citrus flavonoids significantly inhibited amylase-catalyzed starch digestion [50]. Natural alpha-amylase inhibitors offer an attractive approach to the management of postprandial hyperglycemia by decreasing glucose release from starch [51].…”
Section: Inhibition Of α-Amylase Activitysupporting
confidence: 54%
“…In fact, many phenolic compounds and specially flavonoids have been reported as potential antidiabetic agents because they exert a good inhibitory action against α-amylase and could have potential prevention in diabetes mellitus as part of a dietary strategy [49]. These results were confirmed by others studies which showed that all of the tested Citrus flavonoids significantly inhibited amylase-catalyzed starch digestion [50]. Natural alpha-amylase inhibitors offer an attractive approach to the management of postprandial hyperglycemia by decreasing glucose release from starch [51].…”
Section: Inhibition Of α-Amylase Activitysupporting
confidence: 54%
“…Second, we observed that NRG could exert remarkable antihyperglycemic effects (Table 1) in STZ-induced diabetic rats. Its mechanism has multiple components: (i) NRG activates glutathione (GSH) synthesis through a novel antioxidant defense mechanism against excessive ROS production, which contributes to the prevention of oxidative damage in addition to its effect on glycemic control (Dhanya et al 2015); (ii) NRG plays important roles in preventing the progression of hyperglycemia, partly by binding to starch by increasing hepatic glycolysis and the glycogen concentration and lowering hepatic gluconeogenesis (Shen et al 2012); (iii) NRG exhibits antidiabetic effects in a rat model of type 2 diabetes mellitus (T2DM) by potentiating the antioxidant defense system and suppressing pro-inflammatory cytokine production (Mahmoud et al 2012). Third, this study demonstrates the inhibitory effect of NRG on myocardial remodeling and cardiac fibrosis in STZinduced diabetic rats by inhibiting the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plants from this genus have been extensively studied for their antimicrobial, antioxidant, anti-infl ammatory, antiedemic, cardiovascular, antihyperglycaemic, and antitumour properties (Johann et al, 2007;Benavente-Garcia and Castillo, 2008;Fisher and Phillips, 2008;Shen et al, 2012;Mencherini et al, 2013;Wesołowska et al, 2012).…”
Section: Introductionmentioning
confidence: 99%